Antibiotic Sensitivity of Streptococcus Pneumoniae that Isolated from Different Pneumococcal Infections (Indian Journal of Forensic Medicine & Toxicology, 2020)
During the period from June of 2018 to February 2019 (150) isolates of Streptococcus pneumoniae wereisolated from 600 patients with clinical symptoms of Lower respiratory tract infections (LRTI) (pneumonia),otitis media and meningitis obtained from Baqubah Hospitals. The results showed that not only S. pneumoniae causes pneumonia and it can causes diseases other than pneumonia such as otitis media and meningitisbut with less frequency. S. pneumoniae showed different susceptibilities towards antibiotics used in thisstudy. The total susceptibility was (65.8%) and the total resistance was (34.2%). The highest pneumococcalsusceptibility was showed to the cell wall inhibitors (44.4%) followed by protein synthesis inhibitors (28%)and quinolones (17.3%), and the lowest susceptibility was to folate antagonists with 0%. The highest ratesof susceptibility was to penicillin (100%), chloramphenicol (86%), vancomycin (80%) and moderate ratesof susceptibility to levofloxacin (90) 60%, linezolid (42.7) %, cefotaxime (40%), ofloxacin (40%) whereasthere was a relatively lower susceptibility rate towards other antibiotics such as ampicillin, imipenem,amoxicillin, trimethoprim/sulfamethoxazole. Therefore, it should be avoided in the treatment in addition totazobactam, amikacin, gentamicin, which had lowest rates susceptibility against S. pneumoniae. As a result,it required more research to identify new antibiotic or vaccine to reduce the risk of pneumococcal infection.